PENGEMBANGAN SISTEM AUTENTIKASI PENDAFTARAN ONLINE PASIEN PADA KLINIK CATUR ARIWIBOWO MENGGUNAKAN SMS GATEWAY - Siti Sari; Dwi Sakethi; Rizky Prabowo (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2019)
Catur Ariwibowo Clinic is one of health services located in Pringsewu district. Registration services that already exist in the clinic is still conventional, by recording on the book that causes stacking of paper in filing cabinets. One of the utilization of SMS Gateway with Gammu technology is by developing patient online registration authentication system. The purpose of this study is to develop a patient online registration authentication system using SMS Gateway at Catur Ariwibowo Clinic. The development of this system is using waterfall method, with the following stages: requirements definition, system and software design,and Â implementation and unit testing. Functional testing used is Black Box Testing, this test was conducted to find out the system functionality. Researcher use questionnaire to test user satisfaction. Based on the functional test and user satisfaction that has been done, it can be concluded that the system is already running in accordance with its function and 82.56 percent of respondents are satisfied on the system that has been developed.